Treatment of Cystic-Solid Thyroid Nodules with Ultrasound-Guided Radiofrequency Ablation and Enhancement of Thyroid Function - Lou Q; Zhu YF; Ye ML (Journal of Multidisciplinary Healthcare, 2023)
Qin Lou,1,* Yan-Feng Zhu,1,* Mei-Li Ye2 1Department of Ultrasonic Medicine, Affiliated Xiaoshan Hospital, Hangzhou Normal University, HangZhou, People’s Republic of China; 2SHU LAN(QU ZHOU)HOSPITAL, Quzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mei-Li Ye, SHU LAN(QU ZHOU)HOSPITAL, No. 2 Zhong Tower Floor, Fushang Street, Kecheng District, Quzhou, 324000, People’s Republic of China, Tel +8615167059261, Email yemeiliyml6g@126.comObjective: To investigate the efficacy of ultrasound-guided radiofrequency ablation and its effect on thyroid function in patients with cystic-solid thyroid nodules.Methods: We enrolled 90 patients with cystic-solid thyroid nodules and randomly assigned to either a control group (n = 37) or an observation group (n = 53). Patients in the observation group underwent ultrasound-guided radiofrequency ablation, while those in the control group were treated with ultrasound-guided lauromacrogol. Thyroid function was monitored, and complications were recorded for both groups, while nodule reduction rates were compared across a range of volumes and time periods.Results: One month after surgery, the observation group had a larger volume of nodules than the control group, while at 12 months, the volume of nodules in the observation group was smaller. (P < 0.05). Thyroid-stimulating hormone (TSH), free thyroxine 4 (FT4), and free triiodothyronine (FT3) levels were all within normal ranges after treatment in both groups and showed no significant differences from pre-treatment levels. (P > 0.05). There was no statistically significant difference between the total incidence of adverse reactions in the control group (8.11%) and the observation group (5.66%) (P > 0.05).Conclusion: With a low incidence of postoperative adverse reactions, the ultrasound-guided radiofrequency ablation protocol in the clinical treatment of patients with cystic-solid thyroid nodules can effectively reduce the volume of solid thyroid nodules without affecting the thyroid function of patients and can achieve more ideal treatment effectiveness, and is deserving of promotion.Keywords: cystic-solid, radiofrequency ablation, thyroid function, thyroid nodules, ultrasound